GREEN ACCOUNTING ON SUSTAINABILITY INDEX DISCLOSURE IN INDONESIA - Richard Sanjaya; Diana Frederica (ZILLZELL MEDIA PRIMA, 2026)
This study aims to examine the factors influencing sustainability index disclosure among non-cyclical companies listed on the Indonesia Stock Exchange. The factors investigated include management commitment, institutional ownership, and green accounting. Sustainability index disclosure is measured using the Global Reporting Initiative (GRI) Standards 2021. The research data were obtained from annual reports and sustainability reports for the 2023–2024 period. The sample was selected using a purposive sampling method, resulting in 35 non-cyclical companies included in the analysis. Multiple linear regression analysis was employed to assess the effect of each independent variable on sustainability index disclosure. The results indicate that management commitment and institutional ownership have a positive and significant effect on sustainability index disclosure. In contrast, green accounting does not have a significant effect on the level of disclosure. These findings suggest that strong managerial commitment and institutional ownership play a crucial role in encouraging greater transparency in sustainability reporting. However, the implementation of green accounting practices has not yet been fully reflected in sustainability index disclosure. This study contributes to the sustainability reporting literature by highlighting key governance-related factors that influence corporate sustainability disclosure in emerging markets.